Pengaruh Profitabilitas, Likuiditas, Solvabilitas Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern Di BEI - Suprihati; Sri Lestari Yuli (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
This purpose of this research was to determine the effect of profitability, liquidity, solvability, and company size on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018 - 2020. The type of data in this study is secondary (quantitative) data. The total population in this study was 193 company goods industrial sectors, basic and chemical industrial sectors, and various industrial sectors for the period 2018-2020. The number of samples used in this study were 30 companies, using purposive sampling method and data analysis using descriptive statistics and logistic regression. The data is processed using SPSS 23. Simultaneous test results show that profitability, liquidity, solvability, and company size have a significant effect on going concern audit opinion. The partial test results show that only the profitability variable (ROA) has a significant effect on the going concern audit opinion, while the liquidity, solvability, and company size variables have no significant effect on the going concern audit opinion.